Diallyl sulfide alleviates cyclophosphamide-induced nephropathic encephalopathy in rats. (23rd March 2020) - Galal, Shereen M.; Mansour, Heba H.; Elkhoely, Abeer A.
Abstract: Diallyl sulfide (DAS) is a garlic-derived organosulfur compound. The current study was planned to evaluate the protecting effects of DAS against cyclophosphamide (CP)-induced nephropathic encephalopathy. DAS (100 mg/kg) was orally administered for 4 days, 60 min after the last dose, rats were injected with CP (150 mg/kg). DAS treatment before CP significantly decreased serum urea, creatinine, sodium, potassium, calcium, blood urea nitrogen (BUN), C-reactive protein (CRP), interleukin-6 (IL-6), interleukin-1β (IL-1ß) and tumor necrosis factor-alpha (TNF-α) compared with CP-treated rats. DAS treatment decreased malondialdehyde (MDA) and increased superoxide dismutase (SOD) and reduced glutathione (GSH) levels in the renal tissues and significantly attenuated the elevated neurotransmitters N-methyl-D-aspartate/adenosine triphosphate (NMDA), γ-aminobutyric acid (GABA) levels and remarkably restored neuronal nitric oxide (NO) level and nitric oxide synthase (nNOS) activity in the brain compared to CP-treated rats. DAS for 4 consecutive days before CP showed moderate positive immunohistochemically expression of the glial fibrillary acidic protein (GFAP) in the brain and kidney tissues comparable to CP-treated rats. DAS afforded renal and neuroprotection against CP-induced nephropathic encephalopathy due to its capacity to ameliorates the afore-mentioned biochemical parameters which were supported by histopathological and immunohistochemically examination.